Environmental, Social, Governance (ESG) Disclosure and Firm Value: Role of Firm Size - Holly, Anthony; Tangke, Paulus; Kampo, Kunradus; Wijaya, Ricky Alexander (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
The purpose of this study is to investigate the effect of environmental, social, and governance (ESG) disclosure on firm value with firm size as a moderating variable. The theory used is signalling theory and stakeholder theory.This study uses a causal quantitative method with a sample of oil, gas and coal subsector companies listed on the Indonesia Stock Exchange (IDX) between 2021-2023. The sample selection was based on a purposive method, resulting in 61 company samples. The type of data used in this study is quantitative data and analyzed using moderation regression analysis to analyze the dependent variable, firm value, and the independent variable, environmental, social, and governance (ESG) disclosure, as well as the moderating variable, company size. The results of this study indicate that environmental, social, and governance (ESG) disclosure has a positive and significant effect on firm value. Meanwhile, company size is proven to weaken the relationship between environmental, social, and governance (ESG) disclosure on firm value.